Effective Anti-tumor Response by TIGIT Blockade Associated With FcγR Engagement and Myeloid Cell Activation - Han, Jin-Hwan; Cai, Mingmei; Grein, Jeffery; Perera, Samanthi; Wang, Hongmei; Bigler, Mike; Ueda, Roenna; Rosahl, Thomas W.; Pinheiro, Elaine; LaFace, Drake; Seghezzi, Wolfgang; Williams, Sybil M. Genther (Frontiers in Immunology, 2020)
The molecule “T cell immunoreceptor with immunoglobulin and ITIM domain”, or TIGIT, has recently received much attention as a promising target in the treatment of various malignancies. In spite of the quick progression of anti TIGIT antibodies into clinical testing both as monotherapy and in combination with programmed death-1 (PD-1)–directed immune checkpoint blockade, the molecular mechanism behind the observed therapeutic benefits remains poorly understood. Here we demonstrate, using mouse tumor models, that TIGIT blocking antibodies with functional Fc binding potential induce effective anti-tumor response. Our observations reveal that the anti-TIGIT therapeutic effect is not achieved by depletion of intratumoral regulatory T cells or any cell population expressing TIGIT, but instead is mediated by possible “reverse activating signals” through Fcgamma receptors on myeloid cells, inducing expression of various mediators such as cytokines and chemokines. Furthermore, we discovered an induction of a robust and persistent granzyme B and perforin response, distinct from a predominantly interferon-gamma-driven anti-PD-1 blockade. Our observations, for the first time, provide the basis for a mechanistic hypothesis involving the requirement of a functional Fc domain of anti-TIGIT monoclonal antibodies, of which various isotypes are currently under intense clinical investigation.